Morphometric changes on dung beetle Dichotomius problematicus (Coleoptera: Scarabaeidae: Scarabaeinae) related to conversion of forest into grassland: A case of study in the Ecuadorian Amazonia - Marín-Armijos, Diego (2023)
The conversion of forest into grassland can induce differentiation in the functional morphology of resilient species. To assess this effect, we have chosen a dung beetle Dichotomius problematicus, as a model species. We established 20 sampling points distributed along a transect for a forest and grassland located in the Podocarpus National Park in Ecuador. Four pit-fall traps were baited with pig feces per sample point and were left open for 48 h. We sexed and measured 13 morphological traits of 269 individuals. Nonmetric multidimensional scaling was carried out to evaluate the influence of habitat and sexual dimorphism on the traits. We applied a principal component analysis to evaluate the morphological features that best explain the differences between land use and sexual dimorphism. We used generalized linear models to evaluate the explanatory variables: habitat and sexual dimorphism with respect to morphological traits. Five traits contributed over 70% body thickness, Pronotum width, Pronotum length, Head width and Elytra length, following the results of a principal component analysis. Both habitat and sex influence traits. In the forest, the individuals are larger than grassland likely due to available resources, but in grassland, the structures in charge of the burial process head, protibia are larger, displaying a strong pronotum and possible a greater reproductive capacity given by spherecity. These patterns of changes in the size of beetles and their structures could reflect the conservation state of an ecosystem.